Effectiveness of the ABCDEF bundle on delirium, functional outcomes and quality of life in intensive care patients: a study protocol for a randomised controlled trial with embedded process evaluation. Issue 7 (15th July 2021) - Sosnowski, Kellie; Mitchell, Marion; Cooke, Marie; White, Hayden; Morrison, Lynette; Lin, Frances
Abstract : Introduction: Hospital mortality for critically ill patients has decreased significantly throughout the developed world over the past two decades, attributable to improvements in the quality of intensive care, advances in critical care medicine and technologies that provide long-term multiorgan support. However, the long-term outcomes of intensive care unit (ICU) survivors is emerging as a real issue. Cognitive and physical impairments suffered by ICU survivors are common including profound weakness, pain and delirium which are inextricably linked. This study aims to determine the effectiveness of the Assess, prevent and manage pain; Both spontaneous awakening and spontaneous breathing trials; Choice of sedation and analgesia; Delirium: assess, prevent and manage; Early mobility and exercise; Family engagement and empowerment (ABCDEF) bundle in reducing ICU-related short-term and long-term consequences of critical illness through a randomised controlled trial (RCT). Methods and analysis: The study will be a single-centre, prospective RCT. A total of 150 participants will be recruited and randomised to either receive the ABCDEF bundle protocol or non-protocolised standard care for the duration of the participant's admission in the ICU. The primary outcome is delirium status measured using the Confusion Assessment Measure for ICU (CAM-ICU). Secondary outcomes include physical function measured by the Functional Independence Measure and quality of life measured by the European Quality of Life five dimensions, five-level questionnaire. A mixed-method process evaluation will contribute to understanding the experience of health teams who implement the ABCDEF bundle into practice. Ethics and dissemination: Ethics approval was provided by the Metro South Health Human Research Ethics Committee (HREC) (EC00167) and the Griffith University's HREC prior to study commencement. Study results will be disseminated by presentations at conferences and via publications to peer-review journals. Trial registration number: ACTRN12620000736943; Pre-results.